Analysis on influencing factors of heat transfer characteristics of vertical borehole heat exchanger under stratified soil conditions. (April 2023) - Wang, Songqing; Ji, Yuxuan; He, Shijing; Gao, Jing; Wang, Yao; Cai, Xuelong
Abstract: In recent years, factors influencing the heat transfer characteristics of the vertical borehole heat exchanger (BHE) is a hot topic in the research of the ground source heat pump (GSHP) systems. Given the complexities involved in environmental situations with respect to groundwater seepage in saturated soil and moisture migration in unsaturated soil, this paper examined the effects of various influencing factors on the heat transfer characteristics of the vertical BHE under stratified soil conditions, using theoretical research, experimental research, and numerical simulations. Subsequently, through altering five influencing factors—groundwater seepage velocity, porosity, saturation, thermal conductivity, and initial soil temperature—the working conditions of the vertical BHE under stratified soil conditions were established, and the heat transfer rate was calculated. The results showed that the weight of the influencing factors on the heat transfer characteristics of the vertical BHE had a descending order: thermal conductivity, groundwater seepage velocity, porosity, saturation, and initial soil temperature. These results can provide an important reference for further optimizing future BHE designs.